(untitled) (Euro-Asia Conferences, 2021)
In the modern world, when all events and phenomena are developing too quickly, new technologies are being developed and implemented every day, and people are actively using the emerging means of communication, it is impossible to imagine that language as a means of communication is not involved in these processes. It certainly reacts to everything that happens, adapts to the new realities and pace, and reflects the new phenomena that a person faces. That is why, in recent years, linguistics has been moving towards an anthropocentric approach, since a person, a speaker, has long been considered as a central object that produces, changes and adjusts language signs to suit itself, to suit its needs, taking into account its individual traits and characteristics.